A novel variant of C12orf4 in a consanguineous Armenian family confirms the etiology of autosomal recessive intellectual disability type 66 with delineation of the phenotype. Issue 9 (23rd July 2019) - Hancarova, Miroslava; Babikyan, Davit; Bendova, Sarka; Midyan, Susanna; Prchalova, Darina; Shahsuvaryan, Gohar; Stranecky, Viktor; Sarkisian, Tamara; Sedlacek, Zdenek
Abstract: Background: Intellectual disability (ID) is a feature of many rare diseases caused by thousands of genes. This genetic heterogeneity implies that pathogenic variants in a specific gene are found only in a small number of patients, and difficulties arise in the definition of prevailing genotype and characteristic phenotype associated with that gene. One of such very rare disorders is autosomal recessive ID type 66 (OMIM #618221) caused by defects in C12orf4 . Up to now, six families have been reported with mostly truncating variants. The spectrum of the clinical phenotype was not emphasized in previous reports, and detailed phenotype was not always available from previous patients, especially from large cohort studies. Methods: Exome sequencing was performed in a consanguineous Armenian family with two affected adult brothers. Results: The patients carry a novel homozygous nonsense C12orf4 variant. The integration of previous data and phenotyping of the brothers indicate that the clinical picture of C12orf4 defects involves hypotonia in infancy, rather severe ID, speech impairment, and behavioral problems such as aggressiveness, unstable mood, and autistic features. Several other symptoms are more variable and less consistent. Conclusion: This rather nonsyndromic and nonspecific clinical picture implies that additional patients with C12orf4 defects will likely continue to be identified using the "genotype‐first" approach, rather than based on clinical assessment. The phenotype needs further delineation in future reports. Abstract : Intellectual disability (ID) is caused by thousands of genes and variants in a specific gene are found only in a small number of patients. Up to now, six families have been reported with C12orf4 defects causing autosomal recessive ID type 66 (OMIM #618221). Our finding of a novel homozygous nonsense C12orf4 variant in two adult brothers from a consanguineous Armenian family supports the disease association of C12orf4 and shows that its defects cause hypotonia in infancy, rather severe ID, speech impairment, and behavioral problems (aggressiveness, unstable mood, and autistic features), while other symptoms are more variable and less consistent.